The impact of carbon emission disclosure and environmental performance on firm value with good corporate governance as a moderator - Asrorudin, Ahmad; Rosini, Iin; Suripto, Suripto (Institute of Accounting Research and Novation (IARN), 2024)
The purpose of this study is to determine how carbon emission information and environmental performance impact the value of businesses that have good corporate management. Secondary data comes from the financial statements of companies included in the Lq-45 Company Index listed on the IDX from 2018 to 2023. For six years, six companies were used as samples. In this study, panel data regression analysis was used. The results show that carbon emission disclosure has a significant impact on firm value with a negative coefficient, while environmental performance has no significant impact. In contrast, good corporate management cannot control the relationship between environmental performance and carbon recognition. Therefore, it is decided that society does not have much data on greenhouse gas emissions. Very few companies disclose the volume of their GHG emissions; many companies choose to only disclose how much GHG emissions they have reduced. However, not many companies disclose the real value of their GHG emissions, so the market cannot objectively assess how well a company's environmental performance is.